Assessing Pedagogical Practices in Mathematics Using Captured Class Content - Kirkland, Cindi M. (My University, 2012)
This mixed-methods study examined the variability in Exit COMPASS exam scores for Learning Support mathematics students accounted for by Entrance COMPASS exam scores, average chapter exam scores, and time spent reviewing captured class content. The COMPASS exam is a college placement exam in the University System of Georgia that community colleges use to measure a student’s abilities in English, reading, and mathematics. Two-year college students who were required to take Learning Support mathematics courses were provided access to all class content through online recorded sessions. Students also took entrance and exit exams, called COMPASS exams, that were standard throughout the state where the study took place. A correlated t-test analysis revealed that Exit COMPASS exam scores were statistically higher than Entrance COMPASS exam scores. Students made significant gains in knowledge of mathematics, as measured by the COMPASS exam, during the course. However, there was no statistical evidence to prove that academic achievement occurred because of reviewing captured class content. A grounded theory quantitative approach was used to decipher students’ impediments to using technology to review captured class content in a blended learning environment. The results of this study indicate that a blended learning environment may have academic advantages for some students. Further research should be conducted with larger sample populations and fewer limitations to identify effective pedagogical strategies involving reviewing captured class content.
Keywords: Cindi M. Kirkland; Pedagogical Practices; Mathematics; Education; Class Content; COMPASS; Exams; Learning Support; College Placement Exam; Remedial; University System of Georgia